Study of the initiation and development of a pulsed breakdown of short vacuum gaps in the nanosecond time region; Radio Engineering and Electronic Physics; Vol. 14 - Mesyats G. A. Gennady Andreyevich; Bugaev S. P.; Proskurovskii D. I.; Eshkenazi V. I.; Yurike Y. Y. (1969, 1969)
В фонде НТБ ТПУ отсутствует